2020
DOI: 10.7554/elife.58737
|View full text |Cite
|
Sign up to set email alerts
|

mTOR signaling regulates the morphology and migration of outer radial glia in developing human cortex

Abstract: Outer radial glial (oRG) cells are a population of neural stem cells prevalent in the developing human cortex that contribute to its cellular diversity and evolutionary expansion. The mammalian Target of Rapamycin (mTOR) signaling pathway is active in human oRG cells. Mutations in mTOR pathway genes are linked to a variety of neurodevelopmental disorders and malformations of cortical development. We find that dysregulation of mTOR signaling specifically affects oRG cells, but not other progenitor types, by cha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 54 publications
6
66
0
Order By: Relevance
“…Newer rodent models using IUE to focally express or suppress mTORC1 pathway regulating genes in the cortex (discussed more below), as well as Tsc2 and Depdc5 zebrafish models (Kim S. H. et al, 2011;de Calbiac et al, 2018;Swaminathan et al, 2018), also recapitulate many of the mTORopathy phenotypes. Recent models also include patient-derived induced pluripotent stem cells (IPSCs) and cortical organoids, which provide the advantage of studying mTOR function in human cell populations (Blair et al, 2018;Andrews et al, 2020;Dang et al, 2020;Eichmüller et al, 2020). Both transgenic and IUE-based animal models as well as in vitro models have been vital for mechanistic and preclinical drug studies.…”
Section: Designing Animal Models Of Mtoropathiesmentioning
confidence: 99%
“…Newer rodent models using IUE to focally express or suppress mTORC1 pathway regulating genes in the cortex (discussed more below), as well as Tsc2 and Depdc5 zebrafish models (Kim S. H. et al, 2011;de Calbiac et al, 2018;Swaminathan et al, 2018), also recapitulate many of the mTORopathy phenotypes. Recent models also include patient-derived induced pluripotent stem cells (IPSCs) and cortical organoids, which provide the advantage of studying mTOR function in human cell populations (Blair et al, 2018;Andrews et al, 2020;Dang et al, 2020;Eichmüller et al, 2020). Both transgenic and IUE-based animal models as well as in vitro models have been vital for mechanistic and preclinical drug studies.…”
Section: Designing Animal Models Of Mtoropathiesmentioning
confidence: 99%
“…In particular, β-actin mRNA is locally translated near focal adhesions 83 and interestingly, it is the newly synthesized β-actin that is preferentially used in focal adhesion maturation 56 . While global β-actin is less sensitive to cap-dependent translation perturbation [84][85][86][87][88] , this has recently been demonstrated to be cell type and stress dependent [89][90][91] . Indeed, during axon guidance, localized β-actin translation is associated with localized 4E-BP1 hyperphosphorylation 92 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that the absence of the ataxia telangiectasia mutated (ATM) protein in cerebellar astrocytes in culture reshapes their morphology, producing a reduction in the length and number of processes, which in turn negatively regulates the mammalian target of rapamycin (mTOR) pathway [ 33 ]. In addition, it has also been reported that manipulation of mTOR signaling disrupts the glial scaffold in primary cortical and organoid cultures [ 56 ]. These structural changes are associated with abnormal developmental maturation [ 33 , 35 , 36 ] which also alters calcium signaling and affects the cerebellar networks.…”
Section: Discussionmentioning
confidence: 99%